2016
DOI: 10.5005/jp-journals-10012-1151
|View full text |Cite
|
Sign up to set email alerts
|

Implant Design and Stress Distribution

Abstract: Implant design refers to the three-dimensional structure of the implant, with all the elements and characteristics that compose it. Dental implants are subjected to various force magnitudes and directions during function. Because implants function to transfer occlusal loads to the surrounding biologic tissues, functional design objectives should aim to manage biomechanical loads to optimize the implant-supported prosthesis function. Thus, the primary functional design objective is to manage biomechanical loads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…In particular, the results have shown that for the buttress and reverse buttress thread models, the application of curved flanks reduces the maximum von Mises stress by up to 50% compared to straight flanks (Table 5), curved flank provides more bone contact area by decreasing the shear stress and tensile stress. Hence, more bone contact area has been proven to offer increased initial stability and stress resistance [87].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the results have shown that for the buttress and reverse buttress thread models, the application of curved flanks reduces the maximum von Mises stress by up to 50% compared to straight flanks (Table 5), curved flank provides more bone contact area by decreasing the shear stress and tensile stress. Hence, more bone contact area has been proven to offer increased initial stability and stress resistance [87].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the results have shown that for the buttress and reverse buttress thread models, the application of curved flanks reduces the maximum von Mises stress by up to 50% compared to straight flanks (Table 5), curved flank provides more bone contact area by decreasing the shear stress and tensile stress. Hence, more bone contact area has been proven to offer increased initial stability and stress resistance [82].…”
Section: Discussionmentioning
confidence: 99%
“…Among different thread shapes available, including v-shaped, square, buttress, reverse-buttress, and spiral-shaped, the square thread profile provides the best primary stability under immediate loading conditions with highest bone implant contact. Both Misch et al 13 and Yadav et al 14 suggested that in dental implants, shear forces in V-thread and reverse buttress threads are 10-fold higher than in a square thread. This reduction in shear loading at the square thread-bone interface induces more compressive load transfer, which is important in conditions where there is compromised bone density.…”
Section: The Elements Of Osseointegration For Limb Prosthesis 21 | the Implantmentioning
confidence: 99%